Characterization of a novel cytochrome P450 from Amycolatopsis sp. CGMCC1149 for hydroxylation of lovastatin. (7th July 2014) - Zong, Hong; Zhuge, Bin; Lu, Xinyao; Huo, Xiaoyu; Fang, Huiying; Song, Jian; Sun, Jin
Abstract Wuxistatin, a novel and potent statin, is converted from lovastatin by Amycolatopsis sp. CGMCC1149. In the bioconversion, lovastatin is firstly hydroxylated to 3‐hydroxymethyl lovastatin (product I) by a hydroxylase. In the current study, a novel hydroxylase gene p450lov was isolated from Amycolatopsis sp. CGMCC1149 by degenerate PCR and self‐formed adaptor PCR and expressed in Escherichia coli. The gene encodes a 403‐amino‐acid protein with a molecular weight of 44.8 kDa and was designated as a new member of cytochrome P450 (CYP) 105 family, CYP105A44. Meanwhile, a lovastatin catalytic in vitro system was established, and an optimal hydroxylation reaction system contained 30 µM lovastatin, 600 µM NADH, 120 µM ferredoxin, 0.04 U ferredoxin−nicotinamide adenine dinucleotide phosphate reductase, and 100 µM CYP105A44 in a final volume of 200 µL Tris HCl buffer (50 mM, pH 7.4). These would be helpful for further studies on the hydroxylation of statins.